Impact of Pregnant Adolescents’ Knowledge about Preventive Health Behaviors during Pregnancy upon Pregnancy Outcomes in AL- Diwaniyah City - Fadia H. Ali; Hala S. Abdul Wahid; Ekhlas A. Hussein (Indian Journal of Forensic Medicine & Toxicology, 2022)
Objective(s): The aim of the study is to evaluate the impact of pregnant adolescents’ knowledge aboutpreventive health behaviors during pregnancy upon their pregnancy outcomes .Methodology: A quasi-experimental design, using the evaluation approach for the determinationthe impact of pregnant adolescents’ knowledge about preventive behaviors during pregnancy uponpregnancy outcomes in Al-Diwaniyah city from the period 17th January 2020 to 1st June 2021.Non- probability, purposive sample of (35) adolescent pregnant are selected from those who visitAl-Diwanyiah Maternity and Pediatric Teaching Hospital. Data are collected through the use of thestudy instruments (questionnaire) in a form of Google format and through video calls as means of datacollection. Data were analyzed through the use of descriptive statistical data analysis approach andinferential statistical data analysis approach.Results: Results of this study indicate that most of the pregnant are between (16-19) year old (57.1%),(34.3%) are primary school graduates, (71.4%) are housewives, (77.1%) are living in rural area and(80%) are earning an income of (300-600) thousands ID. The overall evaluation of pregnant adolescents’have a lack of knowledge about preventive health behaviors during pregnancy without significantrelationship between pregnant adolescents’ knowledge and their demographic characteristics. As wellas, pregnant adolescents’ knowledge about preventive behaviors during pregnancy does not impose anyeffect upon their pregnancy outcome.Conclusions: The study’s unique finding is that pregnant adolescents have a lack of knowledge aboutpreventive health behaviors during pregnancy, and this knowledge does not have any effect on theirpregnancy outcome.Recommendations: Improving pregnant adolescents’ health literacy is the responsibility of healthcaresystems and healthcare professionals through emphasis by the Ministry of Health role through theantenatal care units to take a part and dissemination of education about the preventive health behaviorsamong pregnant adolescents especially primigravida, and particularly with each specific trimester.